Hearts on the fly [large type] - Shiloh, Toni (Center Point Large Print, 2026)
"Jabari Hall has spent his entire life chasing victory on ice-but one devastating hit leaves him benched, not just from hockey, but from the future he thought he had. Now, as he struggles with deteriorating eyesight, his well-meaning teammates set him up on a date, hoping it will cheer him up-only the date they choose is none other than Val Elliott, his ex's sister. Val never expected to be sitting across from Jabari, especially after the way he broke her sister's heart. But when Jabari opens up about his diagnosis, Val's guarded heart softens, and she offers him a listening ear out of compassion. What begins as a simple friendship quickly turns into something more. As Jabari navigates life off the ice and searches for a new purpose, he's drawn to Val in ways he didn't expect. With her loyalty to her family on the line and Jabari searching for faith and a new purpose, can they make it to the goal together, or will their hearts wind up in the penalty box?"--